Prevention and treatment of venous thromboembolism in pregnancy - Kęsik, Jan Jakub; Zubilewicz, Tomasz; Terlecki, Piotr; Paluszkiewicz, Andrzej; Iłżecki, Marek (Menopause Review/Przegląd Menopauzalny, 2010)
Pregnancy is connected with a higher risk of venous thromboembolism (VTE). The pulmonary embolism (PE) as the most dangerous complication of vein thrombosis (DVT) is the leading cause of maternal death during pregnancy. The development of ultrasonography in diagnosis of vascular disease significantly increased the diagnosis of vein thrombosis also in pregnancy. The aim of this study was to discuss the rules of VTE diagnostics, in particular ultrasonography and to present the recommendations for prevention and treatment of venous thromboembolism in pregnancy.